DEVELOPMENT OF A DIGITAL TWIN OF A DRINK FACTORY: Development of a digital twin of a drink factory - Bolaños Martínez, Geraldine
Digital twins are one of the disruptive technologies introduced since Industry 4.0. The possibility of having a digital representation of a production system provides the opportunity to simulate and perform analysis of industrial processes, detect possible failures before they happen, avoiding corrective maintenance and also the possibility of improving its efficiency by generating operating strategies other than those already established. From the integration of the technical characteristics of the production plants, historical data of their behavior over time and the application of analytical techniques, it is possible to obtain the digital representation of a real system. This article presents the design and implementation of the digital system of a didactic soft drink factory, made up of industrial equipment. The implementation of the digital representation of the didactic factory is carried out, based on the collection of technical data, modeling of parts, adaptation of signals, design of the control strategy, communication between devices and validation of the digital twin, The result obtained is the digital twin, which in appearance and function closely simulates the real plant. With this digital model, it is possible to carry out virtual process start-up techniques and establish communication with the real system.